Soviet preschool education [Forew. by H. Chauncey. Introd. by U. Bronfenbrenner] (Holt, Rinehart and Winston)
Educational Testing Service. H. Chauncey, chief ed. 1.Program of instruction. 1969. XXII, 182 p.